Morphological Characteristics of Arenga pinnata Merr. from Maros and Sinjai Provenances in South Sulawesi, Indonesia, and its relationship with Brix Content. Issue 1 (April 2020) - Nirawati,; Restu, M; Kuswinanti, T; Musa, Y; Paembonan, S A; Millang, S; Syahidah,; Larekeng, S H
Abstract: Palmae is a tree family that has the third biggest potential after the Gramineae and Fabaceae families. Arenga belongs to the genus of the multipurpose palm family (Mogea, Seibert, and Smits 1991), famously known as the "tree of life" and it has high economic potential, especially its sap. The sap produced is the result of photosynthesis which has a high amount of sugar with various inorganic substances and nutrients and good for health. This research provided information regarding the association of sugar content with morphological characteristics and environmental factors, in this case, the intensity of light, humidity and elevation. Morphological parameters observed were stem height, the girth of the bunch, number of green leaves, length of petiole, leaf width (lad), leaf length (pad), number of the female and male inflorescence. Correlation analysis between morphological characters and Brix content showed a moderate correlation on length of the leaf, number of green leaves, and stem height. While the character of environmental factors to Brix content had a moderate correlation on light intensity below the tree stand with a negative correlation value, which was not in line with the value of confidence interval (UpperCI = 0.004) and significantly affected the Brix content.